2005
DOI: 10.1111/j.1523-1755.2005.00157.x
|View full text |Cite
|
Sign up to set email alerts
|

Activation of ERK in renal fibrosis after unilateral ureteral obstruction: Modulation by antioxidants

Abstract: Promotion of tubular epithelial proliferation and survival, and interstitial cell apoptosis, may minimize renal fibrosis after UUO. In the present study, both were linked spatially and temporally with increased pERK expression. Fluvastatin treatment attenuated UUO-induced fibrosis via an antioxidant and pERK-related mechanism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
99
1
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 124 publications
(114 citation statements)
references
References 46 publications
13
99
1
1
Order By: Relevance
“…48,49 Thus, HO-1 activity, through its antioxidant properties, may impair oxidant formation and, hence, reduce EMT. HO-1 protein is upregulated in the obstructed kidney as early as 6 h after UUO and persists up to at least 7 d. 20,21 In this study, HO-1 was expressed in the renal tubules in the sham and CL kidneys of HO-1 ϩ/ϩ mice and was markedly increased in the obstructed kidneys. HO-1 induction has been previously shown to have antifibrotic effects.…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations
“…48,49 Thus, HO-1 activity, through its antioxidant properties, may impair oxidant formation and, hence, reduce EMT. HO-1 protein is upregulated in the obstructed kidney as early as 6 h after UUO and persists up to at least 7 d. 20,21 In this study, HO-1 was expressed in the renal tubules in the sham and CL kidneys of HO-1 ϩ/ϩ mice and was markedly increased in the obstructed kidneys. HO-1 induction has been previously shown to have antifibrotic effects.…”
Section: Discussionmentioning
confidence: 81%
“…The time point was chosen on the basis of previous studies demonstrating that at 7 d, cellular recruitment and growth factor-dependent matrix accumulation have begun and HO-1 is induced. 20,21,60 At the time of killing, both kidneys were removed and cut transversely, and sections were fixed (10% buffered formaldehyde solution) for histopathologic studies or snap-frozen in liquid nitrogen for Western analysis. …”
Section: Animals Surgery and Tissue Preparationmentioning
confidence: 99%
See 1 more Smart Citation
“…71,86 Furthermore, the ERK signaling pathway is activated in UUO and may provide approaches in preventing progression of renal fibrosis. 100,101 As expected, a-SMA expression as well as ERK1/2 phosphorylation, renal fibroblasts proliferation, and activation increased in obstructed kidneys. In vivo, TRPC3 inhibition abrogated these changes, pointing toward an important role of TRPC3 in the pathogenesis of kidney disease simulated by the UUO model.…”
Section: +mentioning
confidence: 78%
“…ERK1/2 is an important mediator of the intracellular signal transduction pathway responsible for collagen synthesis in cardiovascular tissues, including the kidney. 14 Pat et al 29 revealed that tubulointerstitial fibrosis induced by unilateral ureteral obstruction was associated with ERK1/2 phosphorylation in rats. Interestingly, unilateral ureteral obstruction-induced tubulointerstitial fibrosis was reported to be markedly attenuated by treatment with spironolactone, suggesting that aldosterone/MR may contribute to its pathogenesis.…”
Section: Discussionmentioning
confidence: 99%